2014
DOI: 10.5539/mas.v9n2p87
|View full text |Cite
|
Sign up to set email alerts
|

Technique of Tax Rates and Customs Duties Updating as the Tool of Enterprises Innovative Activity Stimulation

Abstract: Purpose: one of the actual economic science problems is the study of the tax loading influence to the economic activity of the managing subjects which are carrying out an innovative activity. Thus an innovative activity of a business is one of the basic factors capable to provide the innovative development of the country as a whole. The article purpose is the study of the approaches directed to the decrease of the managing subjects' tax loading. Methods: in the course of the research the comparative analysis m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…Based on the above aspects, innovation project management is a process of implementing and taking management decisions that are related to defining goals, organizational structure, planning measures and controlling the process of taking them, and aimed at implementing an innovation idea (Nechaev and Antipina, 2015). To our mind, in terms of the innovation project management, the functional method is the most optimal one.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the above aspects, innovation project management is a process of implementing and taking management decisions that are related to defining goals, organizational structure, planning measures and controlling the process of taking them, and aimed at implementing an innovation idea (Nechaev and Antipina, 2015). To our mind, in terms of the innovation project management, the functional method is the most optimal one.…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, the structure of investments over the past decade is quite homogeneous and has a significant raw material component. Financing of innovation activities in developed countries is distributed between public and private sources, this distribution is typical for many European countries [3].…”
Section: Research Questionsmentioning
confidence: 99%
“…The study of the experience of the Russian Federation regions [13,18], and the analysis of works and publications on the management of municipal property and innovations [3,5], showed that at present municipal authorities do not demonstrate any innovative approach to the management of municipal property as a system. This conclusion allowed the author proposing an approach in which the management of municipal property is viewed not as an activity for controlling individual objects but as a system for managing municipal property, the functioning of which is subordinated to the tasks of organizing a modern life support system that meets the requirements of the contemporary innovative market economy of the municipality.…”
Section: Approaches To the Formation Of The Innovative Management Sysmentioning
confidence: 99%